A dose-dependent response to MEK inhibition determines hypoblast fate in bovine embryos - Canizo, Jésica Romina; Ynsaurralde Rivolta, Amanda Eugenia; Vazquez Echegaray, Camila; Suvá, Mariana; Alberio, Virgilia; Aller Atucha, Juan Florencio; Guberman, Alejandra; Salamone, Daniel Felipe; Alberio, Ricardo; Alberio, Ramiro (BioMed Central, 2019)
Background: The segregation of the hypoblast and the emergence of the pluripotent epiblast mark the final stages of blastocyst formation in mammalian embryos. In bovine embryos the formation of the hypoblast has been partially studied, and evidence shows that MEK signalling plays a limited role in the segregation of this lineage. Here we explored the role of different signalling pathways during lineage segregation in the bovine embryo using immunofluorescence analysis of NANOG and SOX17 as readouts of epiblast and hypoblast, respectively. Results We show that SOX17 starts to be expressed in 16–32-cell stage embryos, whereas NANOG is first detected from 8-cell stage. SOX17 is first co-expressed with NANOG, but these markers become mutually exclusive by the late blastocyst stage. By assessing the expression kinetics of NANOG/SOX17 we show that inhibition of MEK signalling can eliminate SOX17 expression in bovine blastocysts, without altering NANOG expression. Modulation of WNT, PKC and LIF did not affect NANOG expression in the epiblast when used in combination with the ERK inhibitor. Conclusions This study shows that SOX17 can be used as a reliable early marker of hypoblast in the bovine, and based on its expression profile we show that the hypoblast segregates in day 7 blastocysts. Furthermore, SOX17 expression is abolished using 1 μM of PD0325901, without affecting the NANOG population in the epiblast. Modulation of WNT, PKC and LIF are not sufficient to support enhanced NANOG expression in the epiblast when combined with ERK inhibitor, indicating that additional signalling pathways should be examined to determine their potential roles in epiblast expansion.